Water treatment in rural India using sunlight and low-cost materials - Porley, Victoria (The University of Edinburgh, 2023)
Access to safe drinking water is essential yet threatened for many, with the United Nations highlighting the importance of providing clean water for all as one of their Sustainable Development Goals to be met by 2030. Provision of drinking water in India is of particular importance, as the majority of the population live in rural areas without sufficient access to water, leading to illnesses which could be easily prevented. The large population and land coverage of the country makes installing widespread centralised water treatment facilities to service all inhabitants extremely difficult, and many households rely on their own means of treating water. Traditional methods of point-of-use water treatment, such as filtration, chlorination and boiling all have limitations, meaning there is a need for finding an improved method. One of the best candidates for such an aim is to use solar driven heterogeneous photocatalysis, whereby a semiconductor material is used to facilitate the generation of reactive oxidising species (ROS), which destroy organic pollutants and pathogens contaminating the water, leading it to be disinfected and safe for human consumption. However, photocatalysis is often limited in its applications due to the reliance on titania (TiO₂) as the catalyst, which requires UV irradiation for efficient generation of the ROS species. Thus, if the material properties of titania can be enhanced through chemical and structural modifications, such that the system is activated by visible light, it will be a highly useful tool for use in rural settings. This is of particular importance as TiO₂ is inexpensive relative to many novel high functioning photocatalysts, such as those based on silver nanoparticles and other materials which are less abundant than Ti or O. It is also biologically and chemically inert, and is frequently produced on an industrial scale for many varied uses. Thus, building on the high efficiency of TiO₂ under UV irradiation with chemical modifications can help to create high functioning visible light-activated photocatalysts that are affordable and non-toxic, making them ideal for such an application. In this Thesis, work has been conducted to address the practical limitations of photo- catalytic water treatment, with the goal of making it suitable for implementing in rural areas on a local, decentralised scale. Field studies were conducted in India, hosted by the Indian Institute of Technology in Kharagpur, during which time catalyst materials were tested with real water samples under solar irradiation, to more closely replicate the conditions in which the treatment method would be used. This helped to build upon lab-scale testing, and highlight areas required for further optimisation. It was found that the catalysts studied (commercial P25 TiO₂ and a bismuth titanate material prepared by previous member of the Robertson research group, Dr Gylen Odling, referred to as BTO-TiO₂) were more successful at removing bacteria from the water samples than solar disinfection alone. However, it was also noticed that there was a significant loss of catalyst over the course of the investigations, and not all could be recaptured. In this study, the catalyst was immobilised on small glass beads, but the adhesion was not as robust as required for the level of use, and the coating would become damaged. Following these field investigations, the main limitations to practical photocatalytic water treatment were highlighted and motived the remaining work for this Thesis. One of the main concerns preventing implementation of such a technique is the difficulty in recapturing the nanopowder catalyst from the water once treatment has been completed. Typically, the catalyst is added as a slurry, which is beneficial for utilising the high surface area of the catalyst, but makes it very difficult to recapture and therefore reuse, as expensive microfilters or centrifuges would be required, adding costs and complexity to the process. The use of glass beads in the field studies improved this and simplified the set-up required, but improvements were still needed. In this work, focus has been given to improving immobilisation of the catalyst powder, primarily focusing on the use of glass as a substrate, whilst adjusting the structure to find a practical balance between costs, surface area, ease of use and robustness of the applied film. Studies were conducted which showed that mixing a suspension of the catalyst with a solution of tetraethyl orthosilicate helped to improve adhesion by forming SiO₂ during sintering, which acted as a glue to hold the catalyst to the surface more effectively. Further, glass chips were used which were formed from ground down used glass bottles, which were successful in replacing glass beads as a high surface area support with lower costs and without the need for intensive chemical pre-treatment to prepare the surface for coating. As well as improving practical aspects, studies were also conducted to explore methods for enhancing the photochemical properties of TiO₂, in order to increase the photocatalytic activity under the whole solar spectrum, not just the UV portion. Firstly, studies focused on attempts to make composites of zinc-iron oxide (ZnFe₂O₄) semiconductors with commercial P25 TiO₂. The synthesis involved adding zinc and iron precursor salts in a solution of ethylene glycol and water in the presence of P25 TiO₂ and either oxalic acid or ammonia to initiate the reaction. It was found that both acid and base methods led to a significant increase in visible light performance, with the base synthesis being the most simple to perform. However, the same high activity was not observed for tests performed under UV or simulated solar irradiation, where the performance was worsened relative to P25 TiO₂. Following this, a different approach was taken, whereby TiO₂ was synthesised in-situ in the presence of bismuth in a reverse-micelle sol-gel approach, in an attempt to build on the success of the BTO-TiO₂ material studied during field testing. This led to much better performance than the ZnFeO/TiO₂ composites, with excellent visible light activity, and UV activity similar to that of P25 TiO₂. The materials were also shown to be stable with repeated use. The materials did not however outperform BTO-TiO₂, which was prepared via a sequential ionic layer adsorption reaction (SILAR) route. SILAR methods have practical limitations that this work attempted to address, and therefore finding the right balance between simplicity of preparation, long-term stability, costs and performance is very important for finding materials suitable for the specific application of solar driven water treatment in rural areas.
Keywords: WATER TREATMENT; RURAL INDIA; SUNLIGHT; LOW-COST MATERIALS; drinking water; reactive oxidising species; ROS; UV irradiation; visible light-activated photocatalysts; photo-catalytic water treatment; slurry; microfilters